2018
DOI: 10.1371/journal.pone.0200389
|View full text |Cite
|
Sign up to set email alerts
|

SeRUN® study: Development of running profiles using a mixed methods analysis

Abstract: ObjectiveTo determine profiles of urban runners based on socio-demographic, health, motivational, training characteristics and running-related beliefs and behaviours.MethodsMixed, exploratory, sequential study with two stages: 1) quantitative, using an online survey; and 2) qualitative, using semi-structured interviews with runners from the previous stage. Participants were recruited via: running routes commonly attended by runners, eight races, previous databases and social media networks. The survey collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 38 publications
(48 reference statements)
1
28
0
9
Order By: Relevance
“…The distance analysis revealed that weekly volume was only a protective factor for 21km and 42km runners. This result might be explained because of the profile of runner who participates in 10km races, with less year of experience and more recreational (Besomi, Leppe, Di Silvestre, & Setchell, 2018). Our findings are consistent with Rasmussen et al (2013), who reported that the relative risk of suffering an injury rose by RR= 2.02 [95% CI: 1.26; 3.24; p < 0.01] among runners with an average weekly training volume below 30 km/week compared with runners with an average weekly training volume of 30-60 km/week.…”
Section: Discussionmentioning
confidence: 99%
“…The distance analysis revealed that weekly volume was only a protective factor for 21km and 42km runners. This result might be explained because of the profile of runner who participates in 10km races, with less year of experience and more recreational (Besomi, Leppe, Di Silvestre, & Setchell, 2018). Our findings are consistent with Rasmussen et al (2013), who reported that the relative risk of suffering an injury rose by RR= 2.02 [95% CI: 1.26; 3.24; p < 0.01] among runners with an average weekly training volume below 30 km/week compared with runners with an average weekly training volume of 30-60 km/week.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in our findings might be due to the study population, study design and definition of running-related injury used. The current study included runners with a high level of running experience (mainly Advanced profile) [ 7 ], and the included race distances were higher (10 km, 21 km and 42 km). Likewise, the frequency of running-related injuries found in this study (7%) was lower than those reported in other studies [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between a new injury and training load was not possible to establish. However, given the high experience level of the population, it is highly likely that runners with greater knowledge about how to manage their training plan can self-manage their running-related symptoms [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature has presented a variety of definitions for different running levels. Studies have suggested standard definitions for different runner levels, which have been derived from subjective questionnaires [ 6 , 7 ]. However, these definitions are often not translated to biomechanical studies examining footwear features for runners.…”
Section: Introductionmentioning
confidence: 99%